The changing nature of how and where Australians play sport - Rochelle Eime; Melanie Charity; Katherine Owen (BMC Public Health)
Abstract Background Understanding participation in sport is important for sport policy, strategy and management. Most research regarding participation in sport report general trends in participation rates. However, as societies trends in leisure-time activities are changing, we need to also understand the settings of sport participation. The aim of this study was to investigate the settings of sport participation of children and adults across 13 major sports in Victoria, Australia. Methods This study utilised data about sport participation collected in the AusPlay survey from a representative sample of adults and children in Victoria, Australia. For each of the 13 sports, the settings of participation were identified for 2020, 2021 and 2022. Respondents can report participation in a particular activity in more than one setting. Therefore, we use the term “instance of participation” to refer to a person playing a particular sport in a particular setting. We calculated the weighted frequencies and prevalences pertaining to sport participation instances in each setting. Results In 2022 compared to 2020, overall participation was 1.1% higher for children and 1.2% higher for adults. For children and adults, the most popular sport for each year was swimming. In 2022, the next most popular sports for children were Australian football, basketball, gymnastics and soccer, and for adults’ tennis, basketball, golf and Australian football. For children, approximately half of participation took place within a sports club or association setting (56-60%). For adults, approximately one third of participation took place within a sports club or association setting (36%). Much of the adult participation took place in non-organised settings. The largest increases in participation in clubs and associations in 2022 compared to 2020 for children was for, hockey, soccer, gymnastics, and Australian football. The adult participation in sports clubs or associations did not fair as well, with 8 sports decreasing the proportion of participation in this setting. Conclusion As a society, we continue to evolve in how we consume participation in sport, and sport policy, infrastructure and opportunities to play need to be directed towards those particular settings and modes of delivery of sport where and how individuals want to play.